Ceci n'est pas un Casino. - Damiani, Didier; Jeck, Marc; Kox, Jo; Muhlen, Kevin; Rauchs, Paul; Reiles, Paul; Steinbrügge, Bettina; Casino Luxembourg - Forum d'Art Contemporain Luxembourg, Luxembourg (Luxembourg : Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2010)
Ardouvin, Pierre ; Barta, Robert ; Bérubé, Patrick ; Bijl, Marc ; Bourgadier, Hermine ; Citizen, Antoinette J. ; Coombs, Courtney ; Dahlgren, Jacob ; Kirps, Paul ; Langelaar, Walter ; Larsson, Annika ; Monk, Ian ; Perbos, Laurent ; Romanini, Letizia ; Thidet, Stéphane ; Val, Olaf
biog. per kunstenaar
Ceci n'est pas un Casino, Casino Luxembourg - Forum d'Art Contemporain Luxembourg, Luxembourg, 1.5. - 5.9.2010
Engels
Frans
boek